Polarographic Study of Stability Constants of Copper(II) Complexes with β-picoline, Malic and Tartaric Acid - Chauhan, P.K.S.; Verma, Amit; Paliwal, R.K. (Asian Journal of Chemistry, 2016)
The mixed ligand complexes of b-picoline (b-pico), malate (mal2–) and tartrate (tart2–) with Cu(II) have been studied polarographically at constant ionic strength (μ = 1.5 M (NaNO3) and pH 5.95 at 25 ± 0.1°C). The reduction of the complexes at d.m.e. is reversible and diffusion-controlled. Two mixed complexes, [Cu(b-pico)(mal)] and [Cu(b-pico)(tart)] are formed. Their stability constants are found to be log b11 = 5.0360 and log b11 = 4.8932, respectively at 25°C.